CONDITIONS OF (I)LEGIBILITY IN THE “LOCAL TURN” IN PEACE PROCESSES: REFLECTIONS FROM THE INDIGENOUS STRUGGLES AROUND THE COLOMBIAN PEACE AGREEMENT - Guerra, Lucas (2022)
The article analyses the called "local turn" in peacebuilding studies, emphasising its centralcharacteristics and main critiques. It also discusses some “local turn” limitations, through a brief analysis of the Colombian peace process, by using the indigenous struggles for participation in the negotiations of the 26/09/2016 Peace Agreement as a tool. As a result, five main elements of criticism to the “local turn” are identified, namely: (1) the inaccuracy about ‘who’ the “local” is; (2) the tendency towards romanticisation and essentialism in the binary opposition between international and local; (3) complacency with the "liberal peace project"; (4) reifications implicated in the "international/ local" binary division; and (5) power relations invisibility and silence that historically shape involved societies. It is concluded that the turn to the local, as aimed by the negotiations for peace in Colombia, remains marked by Eurocentric, state-centered, and neoliberal perspectives.